The Risk Factors, Costs, and Survival Analysis of Invasive VRE Infections at a Medical Center in Eastern Taiwan. (January 2017) - Jiang, Hui-Li; Zhou, Zi; Wang, Lih-Shinn; Fang, Ya; Li, Yi-Hwei; Chu, Cheng-I.
Highlights: Invasive VRE has a high case fatality rate. Invasive VRE cases have a long hospital stay and higher costs of antibiotic use. Active screening in oncology wards is suggested. Abstract: Objective: To analyze 48 cases the risk factors of vancomycin-resistant Enterococcus (VRE) infections, the antibiotic costs after infection, and the survival conditions. Design: 1:3 matched case-control study a medical center in the eastern Taiwan area. The case group, patients with VRE bacterial strains detected at the sterile sites, and the control group were randomly selected from invasive vancomycin-sensitive Enterococcus (VSE) infected patients at the nearest time point by taking the occurrence time of each VRE infection case as the reference time. Fisher exact tests were conducted in order to verify the existence of differences between the case and control groups; survival analysis was applied to explore the prognoses of the VRE infection cases. Results: The mortality rate of the invasive VRE infection cases was 64.6%, which is obviously higher than that of the invasive VSE infection cases (39.4%); the fact of taking chemotherapy during a hospital stay as well as the use of third-generation cephalosporin, glycopeptides, and medicines of the metronidazole category before the infections, are the risk factors of future invasive VRE infections. Moreover, the antibiotic costs after the infections of invasive VRE infection cases are much higher than those of the VSE infection cases (the average daily cost is 3, 433 new Taiwan dollars (NTD) vs. 1, 742 NTD). Conclusions: The history of receiving chemotherapy, the use of third-generation cephalosporin, glycopeptides, and medicines of the metronidazole category before the infections are the risk factors of VRE infections. The antibiotic costs after the infections of invasive VRE infection cases are much higher than those of the VSE infection cases.